2013
DOI: 10.1016/j.jcrs.2012.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Smoothness assessment of corneal stromal surfaces

Abstract: Image texture analysis allowed objective and repeatable assessment of stromal surface roughness; however, full assessments of surface-height fluctuations required 3-D reconstruction. These complementary methodologies offer a more comprehensive assessment of corneal surface roughness in clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Initially, subjective grading of roughness by one or more observers was utilized, however it has been shown that this grading is susceptible to variations in contrast. 9 Objective measures suffer similarly as a change between gray scale values within and between SEM images is not directly related to changes in height; it also represents changes in tilt of the image, surface contamination and enhanced emission from edges and ridges. As such traditional texture analysis or mean grayscale variation methods are not suitable summary measures of the local variation or surface roughness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, subjective grading of roughness by one or more observers was utilized, however it has been shown that this grading is susceptible to variations in contrast. 9 Objective measures suffer similarly as a change between gray scale values within and between SEM images is not directly related to changes in height; it also represents changes in tilt of the image, surface contamination and enhanced emission from edges and ridges. As such traditional texture analysis or mean grayscale variation methods are not suitable summary measures of the local variation or surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…Marian et al have previously described a methodology where a 3D surface is reconstructed and the image flattened to isolate the local variation. 9 However, this methodology requires stereo SEM images and it does not address the issue of enhanced emission from edges. In this article we have used an alternative methodology, the subtraction of the background, which in addition to removing the curvature and tilt information, also removed enhanced emission from edges and ridges, isolating the local variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Image texture, defined as variations in the pixel intensities (variations in the gray-levels), was analyzed using the Haralick texture contrast parameter [25]. The usefulness of this parameter has been well documented in biomedical sciences [26], and more specifically, for the quantification of corneal stromal surface roughness as observed on a SEM image [27]. The Haralick contrast parameter was computed for each SEM image (Matlab R2009b version).…”
Section: Methodsmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) images of deep stromal cuts made by the FS laser have shown an irregular and rougher appearing surface with the appearance of concentric peripheral rings. [ 17 18 19 20 21 22 ] Additionally, there are controversial findings regarding endothelial damage with higher energy settings at deeper layers.…”
mentioning
confidence: 99%